2018
DOI: 10.24251/hicss.2018.679
|View full text |Cite
|
Sign up to set email alerts
|

Scrum in Practice: an Overview of Scrum Adaptations

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
0
15
0
5
Order By: Relevance
“…A small stream of research has examined modifications that are commonly made to scrum [5,27]. Some research has concluded that practitioners will alter scrum to optimize it [27,28]; to respond to requirements [29], or to adapt to distributed teams or larger projects [29]. Agarwal presented a modified scrum methodology adapted to ongoing software delivery [30].…”
Section: Modifications To Scrummentioning
confidence: 99%
“…A small stream of research has examined modifications that are commonly made to scrum [5,27]. Some research has concluded that practitioners will alter scrum to optimize it [27,28]; to respond to requirements [29], or to adapt to distributed teams or larger projects [29]. Agarwal presented a modified scrum methodology adapted to ongoing software delivery [30].…”
Section: Modifications To Scrummentioning
confidence: 99%
“…Nevertheless, these approaches have a high financial and time cost. As a way to address these issues, other approaches [11,12] focus on enhance documentation practices in order to bridge the communication gap.…”
Section: Related Workmentioning
confidence: 99%
“…In order to develop the HCDP application, we adopted the Scrum methodology (Scrum Alliance 2016). Scrum focus on collaborative teamwork and explicitly acknowledge the importance of self-organization and is the most often employed agile methodology (Hron and Obwegeser 2018). We adopted some practices from the Scrum methodology, such as: (i) the products are delivered in increments called "Sprints".…”
Section: Transition Utterancementioning
confidence: 99%